Anaplasmataceae agents among wild mammals and ectoparasites in Brazil - De Sousa, K. C.M. [UNESP]; Calchi, A. C. [UNESP]; Herrera, H. M.; Dumler, J. S.; Barros-Battesti, D. M. [UNESP]; MacHado, R. Z. [UNESP]; André, M. R. [UNESP] (Cambridge University Press (CUP), 2017)
Anaplasmataceae agents comprise obligate intracellular bacteria that can cause disease in humans and animals. Between August 2013 and March 2015, 31 Nasua nasua (coati), 78 Cerdocyon thous (crab-eating fox), seven Leopardus pardalis (ocelot), 110 wild rodents, 30 marsupials, and 42 dogs were sampled in the Pantanal wetland, Brazil. In addition, ectoparasites found parasitizing the animals were collected and identified. The present work aimed to investigate the occurrence of Anaplasmataceae agents in wild mammals, domestic dogs and ectoparasites, by molecular and serological techniques. Overall, 14 (17·9%) C. thous, seven (16·6%) dogs and one (3·2%) N. nasua were seroreactive to Ehrlichia canis. Nine dogs, two C. thous, one N. nasua, eight wild rodents, five marsupials, eight Amblyomma sculptum, four Amblyomma parvum, 13 A. sculptum nymphal pools, two Amblyomma larvae pools and one Polygenis (Polygenis) bohlsi bohlsi flea pool were positive for Ehrlichia spp. closely related to E. canis. Seven N. nasua, two dogs, one C. thous, one L. pardalis, four wild rodents, three marsupials, 15 A. sculptum, two Amblyomma ovale, two A. parvum and one Amblyomma spp. larval pools were positive for Anaplasma spp. closely related to A. phagocytophilum or A. bovis. The present study provided evidence that wild animals from Brazilian Pantanal are exposed to Anaplasmataceae agents.
Keywords: Anaplasma; dogs; Ehrlichia; fleas; qPCR; ticks; wildlife